2010
DOI: 10.1016/j.ejcnurse.2009.10.001
|View full text |Cite
|
Sign up to set email alerts
|

European Cardiovascular Nurses' Experiences of and Attitudes Towards Having Family Members Present in the Resuscitation Room

Abstract: Less than half of the included European cardiovascular nurses had experienced a situation of families being present during resuscitation and protocols pertaining to this were rare. There was no clear attitude towards family presence, though experience in nursing made nurses more favourable towards it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
90
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(95 citation statements)
references
References 25 publications
3
90
0
2
Order By: Relevance
“…Other studies show similar findings: while ones show that the presence of family members during CPR is assessed as beneficial by nurses and/or team members (18)(19)(20) , others show that professionals do not approve it, have no opinion about the matter or never experienced it (20)(21) .…”
Section: Discussionmentioning
confidence: 71%
“…Other studies show similar findings: while ones show that the presence of family members during CPR is assessed as beneficial by nurses and/or team members (18)(19)(20) , others show that professionals do not approve it, have no opinion about the matter or never experienced it (20)(21) .…”
Section: Discussionmentioning
confidence: 71%
“…In contrast, in the other articles that related opinions in favor of this practice, some items stood out as positives: the strengthening of family bonds, facilitation of grieving, avoiding distorted images of care [13,14] , facilitating communication, understanding and acceptance of death, certainty that everything was done, and giving their loved one the opportunity to share in the last moment [13,17] . Even in articles with a strong tendency not to accept this practice, professionals have reported that the presence of the family during CPR may make it easier for the family to accept the death, which is their right, and that there is increased confidence in the team and that it improved professional behavior [23] .…”
Section: Factors That Facilitate the Practicementioning
confidence: 94%
“…Some factors were cited in most studies as a justification for disagreement regarding the presence of the family during CPR, including: the possible increase in stress [1,6,8,11,13,17,18,23] and misunderstanding of the team [6,12,14] decreased concentration and performance of the team [11,13,17] , prolonging the resuscitation time [11,12,14,17,18,23] , psychological trauma [1,11,13,15,20] and distress [12,14] for the family, interference [6,12,15,23,18] or complaints [17] from the family during the procedure, reduced [8,12,15,18,23] or inadequate [13,17,20] space, increase in lawsuits [1, 6, 8, 11-13, 17, 20, 23] and, lack of professionals to provide support to the family [8,12,14,18] . Other less commonly cited factors include: difficulty in teaching students and residents in teachi...…”
Section: Factors That Hinder the Practicementioning
confidence: 99%
See 2 more Smart Citations